Post-harvest nutritional and antioxidant profile of Beta vulgaris L. grown in low emission soilless microgarden system with organic and inorganic nutriments - Ejaz, Shaghef; Jezik , Karoline Maria; Anjum, Muhammad Akbar; Gosch, Christian; Halbwirth, Heidrun; Stich, Karl (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
Beetroot was grown in an open soilless cultivation system with nutrition supplied by organic and inorganic sources. This low emission system was tested for microgardening high quality red beets with high water use efficiency and less pollutant emission in the environs. For this purpose, a pot experiment was planned according to completely randomized design. For inorganically grown red beets, peat moss was combined with 150, 200 and 250 ppm NH4NO3, whereas for organic red beets, peat moss was amended with compost having nitrogen equivalent to the mentioned NH4NO3 concentrations. Rosette and roots were analysed for fresh and dry biomass. Nitrate content, total soluble solids, titratable acidity, ripening index, ascorbic acid, betacyanins, flavonols and antioxidant capacity were assessed as beetroot quality attributes. Combination of peat moss with NH4NO3 showed comparatively lower fresh plant biomass, fresh and dry biomasses of rosette and root, and root to rosette ratio. However, enhanced antioxidant activity and bioaccumulation of ascorbic acid, total soluble solids, betacyanins, flavonols and reduced titratable acids, resulting in higher ripening index and good quality were observed in peat moss combined NH4NO3 treated beetroots. Overall, combination of peat moss with NH4NO3 led to higher nutritional and antioxidant quality of red beet plants.